الأهمية الفنية الجنائية لكشف آثار الأسلحة النارية - المعز هارون محمد ابراهيم (White Nile Journal for Studies and Research, 2023)
The aim of this study is to investigate the forensic significance of detecting the traces of firearms from a jurisprudential and legal perspective. The study includes an introduction that discusses the reasons, objectives, and importance of the topic, as well as the scope of the research, its problems, hypotheses, and the methodology used in writing the research. The study consists of two sections: the first section explores the types and effects of firearms, while the second section focuses on the forensic importance of detecting the traces of firearms. At the end of the research, the researcher reaches important findings and recommendations. For example, taking into account the results of modern evidence in proving cases helps strengthen the pillars of justice, establish security and stability in society, and achieve the objective of preserving people's lives, honor, and property from assault and safeguarding them from violations. One of the recommendations is to establish specialized institutes and research centers to study modern physical evidence in proof from various scientific, legal, and judicial perspectives. This will lead to results, recommendations, and proposals that greatly contribute to understanding the reality and nature of modern physical criminal evidence. Expertise in firearm residues: The process of firearm discharge leaves behind various physical effects, such as empty casings, bullet heads, and burnt gunpowder residues, among others. Scientific expertise plays a role in identifying the firearms from which the empty casings found at the crime scene were fired, as well as extracting bullet heads from the bodies of victims. By comparing them with samples of suspected firearms, the firearms used can be definitively and decisively identified. Additionally, conducting tests on firearm residues and burnt gunpowder residues found on the hands of shooters is very useful in investigating cases of suicide and other crimes.